A Realis Subjunctive in German. (12th August 2020) - Csipak, Eva
Abstract: The German Konjunktiv II is known for its reportative and irrealis uses. This paper argues for a third, realis, use which is independent of the other two uses. Thus by uttering ' Da wäre Saft im Kühlschrank there is.[realis subjunctive] juice in the fridge' a speaker can signal that not only is she certain that there is juice in the fridge, but also that she is offering the juice to an interlocutor. I show that the meaning contribution of the realis subjunctive is strictly not-at-issue, and I develop a multi-dimensional formal semantics that captures both the distribution of the realis subjunctive, and its interaction with operators such as negation and tense. The conditions of use of the construction are modelled in terms of decision theory.